High SNR Gain by Stochastic Resonance in a Tristable System - Pin Wan; Yi-Ju Zhan; Hui Zheng; Luo-Ya Zeng; Qin Deng (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
We report that the signal-to-noise ratio (SNR) can be improved by the stochastic resonance (SR) in a tristable system. The system is driven by Gaussian white noise and a sinusoidal signal, and studied by using the second-order Runge-Kutta method. We find that the SNR gain exhibits the stochastic resonance behavior, and greatly exceeds unity on some occasions. This result is the latest development of the tristable stochastic resonance, and has potential applications in the signal detection, processing and communications.  DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3712